Alterations of the Hippocampal Neurogenic Niche in a Mouse Model of Dravet Syndrome - Martín-Suárez, Soraya; Abiega, Oihane; Ricobaraza, Ana; Hernandez-Alcoceba, Rubén; Encinas, Juan Manuel (Frontiers in Cell and Developmental Biology, 2020)
Hippocampal neurogenesis, the process by which neural stem cells (NSC) continuously generate new neurons in the dentate gyrus of most mammals including humans, is chiefly regulated by neuronal activity. Thus, severe alterations have been found in samples from epilepsy patients and in the hippocampal neurogenic niche in mouse models of epilepsy. Reactive-like and gliogenic NSCs plus aberrant newborn neurons with altered migration, morphology and functional properties are induced by seizures in experimental models of temporal lobe epilepsy. Hippocampal neurogenesis participates in memory and learning and in the control of anxiety and stress. It has been therefore hypothesized that part of the cognitive symptoms associated with epilepsy could be promoted by impaired hippocampal neurogenesis. We here analyze for the first time the alterations of the neurogenic niche in a novel mouse model of Dravet Syndrome (DS), a genetic encephalopathy with severe epilepsy in infancy and multiple neurological comorbidities. Scn1aWT/A1783V mice, hereafter referred to as DS, carrying a heterozygous and clinically relevant SCN1A mutation (A1783V) recapitulate the disease at the genetic and phenotypic levels. We demonstrate that in the neurogenic niche of young adult DS mice there are less NSC, they have impaired cell division and bear reactive-like morphology. In addition, there is significant aberrant neurogenesis. Newborn immature neurons migrate abnormally, and several morphological features are drastically changed. Thus, this study shows for the first time important modifications in hippocampal neurogenesis in DS and opens venues for further research on this topic.